If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -20p = -2(p + 2) + 4p Reorder the terms: 20 + -20p = -2(2 + p) + 4p 20 + -20p = (2 * -2 + p * -2) + 4p 20 + -20p = (-4 + -2p) + 4p Combine like terms: -2p + 4p = 2p 20 + -20p = -4 + 2p Solving 20 + -20p = -4 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. 20 + -20p + -2p = -4 + 2p + -2p Combine like terms: -20p + -2p = -22p 20 + -22p = -4 + 2p + -2p Combine like terms: 2p + -2p = 0 20 + -22p = -4 + 0 20 + -22p = -4 Add '-20' to each side of the equation. 20 + -20 + -22p = -4 + -20 Combine like terms: 20 + -20 = 0 0 + -22p = -4 + -20 -22p = -4 + -20 Combine like terms: -4 + -20 = -24 -22p = -24 Divide each side by '-22'. p = 1.090909091 Simplifying p = 1.090909091
| ln(x+4)-ln(x-6)=ln(17) | | 3.5d+9.25=7+4.25d | | a^4+3a-a^2=-28 | | s=y-(100+0.78y) | | -3n-(-4)/-6=12 | | 64-12*2-6/3 | | 20x-10x^2=1200 | | -3n-(-4)/6=12 | | 5(2w+1)-9= | | -5(y-6)+2(3y-4)=-10 | | 9x+102=0 | | (R-3)/3=5 | | 2+21=x+10 | | -101/3(93) | | -4x+10(3-4x)=11x+6(5+2x) | | 4+(k+5)=13 | | -4(x+2)+6x= | | 3(d+2)=-3d-12 | | -42=-6/7w | | 9-h-15=93 | | 25+m=-6 | | 3+5p=95 | | -(v+5)+5(2v-6)= | | -2(x-1)=8x+32 | | 3x+8=10x-3 | | 3(2t-4)+2t=24+t | | D+-1=-19 | | 9y+3+4y=-23 | | -8=5u+7 | | f^-1(4)=3x-4/5 | | X=7y+6 | | X=7y+y |